2022
DOI: 10.32358/rpd.2022.v8.589
|View full text |Cite
|
Sign up to set email alerts
|

Public transport accessibility to hospitals in the city of Córdoba: a comparative analysis in times of a pandemic (2019-2021)

Abstract: Purpose: to evaluate the potential accessibility to public hospitals between 2019 and 2021. Methodology/Approach: comparative analysis of travel times by public transport, calculated using the r5r package in R with the GTFS provided by the municipality. Findings: for the three hospital categories evaluated, travel times increased around 20% in the study period, and the most vulnerable quintiles of population increased their travel times 8 points above the less vulnerable quintiles. Research Limitation/implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 26 publications
4
9
0
Order By: Relevance
“…If the comparison is made between both study years, the mean value indicated in the boxplots of Figure 4 shows lower travel times for 2023 than for 2022, and the spread of the estimations also seems smaller for 2023. These general tendencies were also observed in the work of Martinazzo and Falavigna (2022), as described in Section 2.4, and are confirmed by the principal statistics in Table 2. The difference in average travel times between Q1 and Q5 is around 15 min for 2022 and 14 min for 2023.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…If the comparison is made between both study years, the mean value indicated in the boxplots of Figure 4 shows lower travel times for 2023 than for 2022, and the spread of the estimations also seems smaller for 2023. These general tendencies were also observed in the work of Martinazzo and Falavigna (2022), as described in Section 2.4, and are confirmed by the principal statistics in Table 2. The difference in average travel times between Q1 and Q5 is around 15 min for 2022 and 14 min for 2023.…”
Section: Resultssupporting
confidence: 79%
“…The function also has arguments that can be set by the user, such as modes, departure date and time, time window, percentiles, maximum walking, biking, or by car time, maximum trip duration, fare structure, and max fare to consider monetary constraints, average walking or biking speed, among others. As selected in the previous Martinazzo and Falavigna's (2022) work, the analyzed time window was between 9 and 11 in the morning, and the departure date was set on an April Wednesday in 2022 and 2023. The maximum walking time was 10 min, equivalent to the 833 m walk used in the cited work, the maximum trip duration was 120 min, and the percentile selected was 85, meaning 85% of trips between every origin and destination pair are shorter than the obtained result.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations